Highlights of the ERS Lung Science Conference and Sleep and Breathing Conference 2021 and the new ECMC members - Goodwin, Amanda T. (2021)
This article provides a brief description of some of the most remarkable sessions of the @EuroRespSoc Lung Science Conference and the Sleep and Breathing Conference 2021 and presents the new incoming members of the ECMC (@EarlyCareerERS). The Lung Science Conference (LSC) and the Sleep and Breathing Conference (SBC) are two conferences organised by the European Respiratory Society (ERS), the latter held in association with the European Sleep Research Society. This year, the LSC and SBC were both held in a virtual format with the participation of researchers and clinicians from around the world. The participation of Early Career Members (ECMs) was notable in both events: 216 of 363 (60%) delegates attending the LSC were under 40 years old, and 315 of 920 (34%) delegates were ≤40 years of age at the SBC. Both conferences included outstanding talks on the most recent advances in respiratory medicine and science, oral/poster communication sessions on novel research, exciting opportunities to network with peers, and much more! This paper provides a brief overview of some of the most remarkable sessions of the LSC and SBC, written by ECMs attending the sessions.